Logic and the Foundations of Game and Decision Theory (LOFT 7) - van der Hoek, Wiebe; Bonanno, Giacomo; Wooldridge, Michael (Texts in Logic and Games, 2008)
This volume collects together revised papers originally presented at the 7th Conference on Logic and the Foundations of Game and Decision Theory (LOFT 2006). LOFT is a key venue for presenting research at the intersection of logic, economics and computer science, and the present collection gives a lively and wide-ranging view of an exciting and rapidly growing area.